CSA bundle 3: Scaling climate-smart inputs and agricultural practices in Zambia - Agova (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
The consortium proposes a 24-month action to strengthen the climate resilience of the groundnut, maize, and soybean value chains in southern, central, and eastern Zambia. Led by Agova, with support from Seed Co, PlantCatalyst, iDE, and the Zambian Agricultural Research Institute (ZARI), the project will improve access to climate-smart inputs, services, and output markets for 10,000 smallholders, including women and young farmers. This includes Seed Co[1]produced climate-smart foundation seed varieties together with natural growth-agent PlantCatalyst; climate information services (CIS); training on climate-smart agriculture (CSA); and improved linkages to sustainable financing and market off-takers. Together, Seed Co and PlantCatalyst will develop and market its combined input package and support uptake through technical training. ZARI will lead on variety selection and on-farm trials to evaluate research findings. Farmers will be drawn from iDE’s network, with the organization leading on CSA training and seed-system formalization through capacitation of seed multipliers and Community Agents (CAs). Agova will oversee project management alongside monitoring, evaluation, and learning (MEL). Key deliverables include CSA farmer field schools (FFS) and demonstration days; seed fairs and distribution of Seed Co-PlantCatalyst input packages, training on technical extension and CIS for CAs; radio broadcasts to advertise inputs and disseminate climate/meteorological reports; and relationship facilitation between smallholders, capital providers, and market actors.